Feminist judgments : health law rewritten / edited by Seema Mohapatra, Lindsay F. Wiley. - Wiley, Lindsay F., 1977-; Mohapatra, Seema (Feminist judgments series., 2022)
This volume provides an alternate history of health law by rewriting key judicial opinions from a feminist perspective. Each chapter includes a rewritten opinion penned by a leading scholar relying exclusively on court precedents and scientific understanding available at the time of the original decision accompanied by commentary from an expert placing the case in historical context and explaining how the feminist judgment might have shaped a different path for subsequent developments. It provides a map of the health law field-where paternalism, individualism, gender stereotypes, and tensions over the public-private divide shape decisions about informed consent, medical and nursing malpractice, the relationships among health care professionals and the institutions where they work, end-of-life care, reproductive health care, biomedical research, ownership of human tissues and cells, the influence of religious directives on health care standards, health care discrimination, long-term care, private health insurance, Medicaid coverage, the Affordable Care Act, and more.